Ambient nitrogen oxides exposure and early childhood respiratory illnesses - Ghosh, Rakesh; Joad, Jesse; Benes, Ivan; Dostal, Miroslav; Sram, Radim J; Hertz-Picciotto, Irva (Environment international, 2012)
Acute respiratory infections are common in children below 5 years and recent studies suggest a possible link with air pollution. In this study, we investigated the association between ambient nitrogen oxides (NO(x)) and bronchitis or upper airway inflammation. This longitudinal study was conducted in Teplice and Prachatice districts, Czech Republic. Children were followed from birth to 4.5 years of age. Data were compiled from medical records at delivery and at follow up, and from self-administered questionnaires from the same two time points. Air pollution monitoring data were used to estimate exposure over five different averaging periods ranging from three to 45 days prior to an episode. To quantify the association between exposure and outcome, while accounting for repeated measure correlation we conducted logistic regression analysis using generalized estimating equations. During the first 2 years of life, the adjusted rate ratio for bronchitis associated with interquartile increase in the 30-day average NO(x) was 1.31 [95% confidence interval (CI): 1.07, 1.61] and for two to 4.5 year olds, it was 1.23 (95% CI: 1.01, 1.49). The 14-day exposure also had stable association across both age groups: below 2 years it was 1.25 (95% CI: 1.06, 1.47) and for two to 4.5 years it was 1.21 (95% CI: 1.06, 1.39). The association between bronchitis and NO(x) increased with child's age in the under 2 years group, which is a relatively novel finding. The results demonstrate an association between NO(x) and respiratory infections that are sufficiently severe to come to medical attention. The evidence, if causal, can be of public health concern because acute respiratory illnesses are common in preschool children.
Keywords: veřejné zdravotnictví; Female; Infant; předškolní dítě; novorozenec; bronchitida; oxidy dusíku; ženské pohlaví; monitorování životního prostředí; Epidemiological Monitoring; longitudinální studie; znečištění ovzduší; lidé; Air Pollution; Infant, Newborn; Bronchitis; inhalační expozice; Nitrogen Oxides; kohortové studie; Public Health; Cohort Studies; epidemiologické monitorování; Male; Air Pollutants; kojenec; Czech Republic; Child, Preschool; Respiratory Tract Diseases; Environmental Monitoring; Česká republika; mužské pohlaví; látky znečišťující vzduch; nemoci dýchací soustavy; Inhalation Exposure; Longitudinal Studies; Humans